2012
DOI: 10.1163/156914912x620833
|View full text |Cite
|
Sign up to set email alerts
|

The English-Only Movement in the US and the World in the Twenty-First Century

Abstract: In this article, I examine the English-only movement in the United States and other countries in the fijirst decade of the twenty-fijirst century. Elaborating on research on the hegemony of English, this examination demonstrates English-only ideology, both linguistic and visual, as a primary means of restricting language and ethnic minorities' access not only in the US, but also globally. First, I will present English as a social construction of the Anglo-Saxon elites in the process of the subordination of other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Despite the United States not having a federal official language, de facto, and in the mind of many Americans, it does. The prevalence of the "English-Only Movement" is wide, and anti-Latinx sentiment can be very public and at times quite vitriolic (Pac, 2012). Despite 75% of the aforementioned 37 million Spanish speakers claiming they speak English "very well" or "well," the fact that they speak Spanish at all, rather than being monolingual English speakers, is viewed as un-American to many (ibid.).…”
Section: La Politique Des Microcentres/the Politics Of Micro-centers Transnational Translationmentioning
confidence: 99%
“…Despite the United States not having a federal official language, de facto, and in the mind of many Americans, it does. The prevalence of the "English-Only Movement" is wide, and anti-Latinx sentiment can be very public and at times quite vitriolic (Pac, 2012). Despite 75% of the aforementioned 37 million Spanish speakers claiming they speak English "very well" or "well," the fact that they speak Spanish at all, rather than being monolingual English speakers, is viewed as un-American to many (ibid.).…”
Section: La Politique Des Microcentres/the Politics Of Micro-centers Transnational Translationmentioning
confidence: 99%
“…For many, the English language symbolizes a national identity, and English Only measures seek to target linguistic and ethnic groups via education; particularly in times of influx of immigrant populations (Pac, 2012). This phenomenon is clearly visible along the historical timeline beginning with the prohibition of native languages of enslaved Africans, the creation of Indian Boarding Schools, school segregation of ethnic minorities in the 1960s and 1970s, and the current resurgence targeting Spanish speakers today (Pac, 2012;Stewart, 2005).…”
Section: The English Only Movementmentioning
confidence: 99%
“…For many, the English language symbolizes a national identity, and English Only measures seek to target linguistic and ethnic groups via education; particularly in times of influx of immigrant populations (Pac, 2012). This phenomenon is clearly visible along the historical timeline beginning with the prohibition of native languages of enslaved Africans, the creation of Indian Boarding Schools, school segregation of ethnic minorities in the 1960s and 1970s, and the current resurgence targeting Spanish speakers today (Pac, 2012;Stewart, 2005). Even as national policies have attempted to obligate federally funded agencies to provide language services to the Spanish-speaking population, English Only initiatives have managed to force English language instruction in states such as California, Arizona, and Massachusetts (Proposition 203, 2000;Proposition 227, 1998;Question 2, 2002).…”
Section: The English Only Movementmentioning
confidence: 99%
“…English and its dominant status are a socially and politically motivated construct (P. A. Cooper 1989;Pac, 2012;Skutnabb-Kangas & Phillipson, 2010). Although the notion of English as the dominant language was enforced using English in every domain of public life, the concept of minority languages was developed through erasure by the conflation of language with ethnicity and by the devaluation of minor language/English bilingualism (García & Mason, 2009).…”
Section: Language Identity -Linguistic Justicementioning
confidence: 99%
“…Although the notion of English as the dominant language was enforced using English in every domain of public life, the concept of minority languages was developed through erasure by the conflation of language with ethnicity and by the devaluation of minor language/English bilingualism (García & Mason, 2009). Pac (2012) conducted a study on the English-only movement in settler United States and other countries in the first decade of the 21st century. An important finding from this study suggested a reemergence of the English-only movement appealing to nationalist sentiments to diminish language and ethnic minorities' rising political presence in the United States in the 21st century.…”
Section: Language Identity -Linguistic Justicementioning
confidence: 99%